'We Learned the Language of the Tree' Ecovillages as Spaces of Place-Based Transformative Learning. (January 2023) - Pisters, Siri R.; Vihinen, Hilkka; Figueiredo, Elisabete; Wals, Arjen E. J.
This article explores learning processes that underpin ecovillages as place based 'sustainability initiatives'. Through the theoretical lens of place- based transformative learning (PBTL), developed in earlier work (Pisters et al., 2019, 2020 ), empirical data from life-story interviews and photovoice sessions from three ecovillages is analysed and discussed. The results support, illustrate and deepen the meaning of the four dimensions of the theoretical framework: connection to place, compassionate connection, creativity and transgression. They show how the co-existence of 'community' and 'disruption' is essential in PBTL where community brings connection, cohesion and stability to a change process whereas disruption paves the way for disrupting old structures and experiment with new ones. This article shows how a change in inner consciousness is related to alternative practices and structures that re-define relationships with ourselves, other humans and the material, more-than-human world.